Profile of Junior High School Students' Mathematical Abstraction in Forming the Concept of Triangles - Febrina Hajiroh; Rita Lefrida; Muh Rizal; Mubarik Mubarik (JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study aims to describe the profile of junior high school students' mathematical abstraction in forming the concept of triangles in terms of high, medium, and low levels of mathematical ability, based on the stages of RBC+C, namely recognizing, building-with, constructing, and consolidation. This study uses a descriptive qualitative approach with three seventh-grade students as subjects, one student each with high, medium, and low mathematical ability, selected based on the results of a mathematical ability test. Data were collected through triangle abstraction assignments and interviews, then analyzed using the Miles and Huberman model which includes data condensation, data presentation, and drawing and verifying conclusions. The results showed that students with high mathematical ability were able to pass all stages of RBC+C optimally, students with medium ability were able to reach all stages but not optimally, while students with low ability experienced limitations in almost all stages of mathematical abstraction, especially in the aspects of building-with, constructing, and consolidation. Thus, the level of students' mathematical ability significantly influences the quality of the mathematical abstraction process in forming the concept of triangles.